2013
DOI: 10.1117/12.2031088
|View full text |Cite
|
Sign up to set email alerts
|

Thin fused silica optics for a few arcsec angular resolution and large collecting area x-ray telescope

Abstract: The implementation of a X-ray mission with high imaging capabilities, similar to those achieved with Chandra (< 1 arcsec Half Energy Width, HEW), but with a much larger throughput is a very attractive perspective, even if challenging. For such a mission the scientific opportunities, in particular for the study of the early Universe, would remain at the state of the art for the next decades. At the beginning of the new millennium the XEUS mission has been proposed, with an effective area of several m 2 and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Fused silica has been widely used to make precision lenses and optics because of its low thermal expansion and excellent optical transmission in a broad spectrum from ultraviolet to near infrared. 1,2,4 For example, it has been extensively used to fabricate large-aperture (~0.5 to 1.0 m) optics in the National Ignition Facility (NIF) 2 and the Chinese high-power laser system. 3 Reducing power loss and increasing the laser-induced damage threshold, require the manufacture of these optics with an ultra-low form error (RMS ≤60/λ), an ultra-smooth surface (Ra ≤5 nm) and a damage-free surface/subsurface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fused silica has been widely used to make precision lenses and optics because of its low thermal expansion and excellent optical transmission in a broad spectrum from ultraviolet to near infrared. 1,2,4 For example, it has been extensively used to fabricate large-aperture (~0.5 to 1.0 m) optics in the National Ignition Facility (NIF) 2 and the Chinese high-power laser system. 3 Reducing power loss and increasing the laser-induced damage threshold, require the manufacture of these optics with an ultra-low form error (RMS ≤60/λ), an ultra-smooth surface (Ra ≤5 nm) and a damage-free surface/subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…Fused silica has been widely used to make precision lenses and optics because of its low thermal expansion and excellent optical transmission in a broad spectrum from ultraviolet to near infrared . For example, it has been extensively used to fabricate large‐aperture (~0.5 to 1.0 m) optics in the National Ignition Facility (NIF) and the Chinese high‐power laser system .…”
Section: Introductionmentioning
confidence: 99%
“…At MSFC, we are involved in several technology development efforts for higher resolution, larger area, and lighter weight x-ray optics to support future replacement of the 15-year-old Chandra X-ray Observatory, [1][2][3][4] with the next mission to attain sub-arcsecond x-ray imaging. All of these technologies [5][6][7][8][9][10][11][12][13][14][15] share the need to be mounted, assembled, and aligned into modular units for testing or for flight. Because in our recent experience with moderate-resolution optics [16][17][18][19][20] we have found that without considerable development effort, it is difficult to prevent structure induced errors from contributing significantly, i.e.…”
Section: Introductionmentioning
confidence: 99%